The mental representation of occupational stereotypes is driven as much by their affective as by their semantic content - Ferenc Kocsor; Tas Ferencz; Zsolt Kisander; Gitta Tizedes; Blanka Schaadt; Rita Kertész; Luca Kozma; Orsolya Vincze; András Láng (BMC Psychology, 2022)
Abstract Background Studies on person perception showed that stereotypes can be activated by presenting either characteristic traits of group members, or labels associated to these groups. However, it is not clear whether these pieces of semantic information activate negative and positive stereotypes directly, or via an indirect cognitive pathway leading through brain regions responsible for affective responses. Our main objective with this study was to disentangle the effects of semantic and affective contents. To this end, we intended to scrutinize whether the representation of occupational labels is independent of the emotions they evoke. Methods Participants (N = 73, M = 27.0, SD = 9.1, 31 men 42 women,) were asked to complete two tasks presented online. In the first task they had to arrange 20 occupational labels—randomly chosen from a pool of 60 items—in a two-dimensional space, moving the mouse pointer along two undefined axes. In a second task the axes’ names were defined a priori. Subjects were asked to arrange the labels according to valence, the extent to which the word evoked pleasant or unpleasant feelings, and arousal, the extent to which the word evoked excitement or calmness. Results Based on the final coordinates of the labels, two cluster analyses were carried out separately in the two tasks. The two clusters were compared with Fisher’s exact test, which revealed that the cluster structures overlap significantly. Conclusions The results suggest that the spontaneous categorization and the semantic representation of occupations rely largely on the affective state they evoke. We propose that affective content might have a primacy over detailed semantic information in many aspects of person perception, including social categorization.